Evaluation of vascular invasion in hepatic alveolar echinococcosis using computed tomography: An observational study - Ilyar A. Baudinov; Aliya I. Kadyrova; Kanat Omorov; Bakhadyr K. Bebezov; Kubat Ibraimov; Aleksei Oginskiy; Roshan Kumar Shah; Shabdan N. Isamadyrov (Heart Vessels and Transplantation)
Objective: Alveolar echinococcosis (AE) is a severe, chronic parasitic disease predominantly affecting the liver. Surgical intervention is the only definitive treatment, but vascular invasion significantly increases surgical risks. This study aimed to identify factors associated with vascular invasion in hepatic AE to improve diagnosis and surgical planning.